THE SOCIAL NECESSITY OF MEASURES TO COMPENSATE FOR THE DAMAGE CAUSED BY FRAUDULENT CRIMES (World Bulletin of Management and Law, 2022)
Intolerance of fraudulent crimes, ensuring that those who commit them are brought to justice, repairing the damage caused, and their impact on the social environment, which poses a variety of risks, are currently relevant.
Keywords: Fraud; cyber-attack; victim; “trend”